De renda e de pele: fazeres com fio - marcas do contato - Sandoval, Andrea Liliana Rey (2018)
Of lace and skin is a research about an immersion in search of characteristic artisanal expressions in the state of Ceará, Brasil, specifically the bobbin lace. Here, I recount an experience in which I did appropiations of pieces made by local artisans that developed into a number of artistic works where I explored the plastic correlation between the cloth and the human skin, their markings and the tangible and poetic connection of both surfaces with the sense of touch. This journey also allowed me to reflect upon my creative process and the procedures I had used previously. Consequently, I was able to apply and share them in this search, something that was possible due to a method that gave importance to the practice and the sharing of knowledge within a research group. In the same way, I brought to discussion the voice of some theorists that fostered and gave consistence to my reflections, and also artists who share my work, either for using the same material (cloth – thread) or for the creation patterns they employ.